2012
DOI: 10.1007/s00259-012-2065-4
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT changes therapy management in high-risk DTC after first radioiodine therapy

Abstract: (18)F-FDG PET/CT resulted in a change of therapeutic procedure in 11 of 90 patients and in a change of patient management through additional diagnostic measures in 8 of 90 patients, and is consequently very helpful in initial staging. At our hospital, (18)F-FDG PET/CT in high-risk patients with differentiated thyroid carcinoma has been established as an initial staging modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 26 publications
4
61
0
4
Order By: Relevance
“…Razfar et al evaluated the likelihood that a PET scan would change management in this scenario, and found that a PET scan changed the treatment plan in 28.2% of cases, which is similar to the present findings (21). There is a smaller body of literature describing the use of the PET scan for initial staging in intermediate-to high-risk patients with conflicting conclusions regarding its utility (10,22). Others have described the use of the PET scan in the evaluation of patients with persistently elevated thyroglobulin antibodies, and found about half of patients have disease identified on a PET scan (14,15).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Razfar et al evaluated the likelihood that a PET scan would change management in this scenario, and found that a PET scan changed the treatment plan in 28.2% of cases, which is similar to the present findings (21). There is a smaller body of literature describing the use of the PET scan for initial staging in intermediate-to high-risk patients with conflicting conclusions regarding its utility (10,22). Others have described the use of the PET scan in the evaluation of patients with persistently elevated thyroglobulin antibodies, and found about half of patients have disease identified on a PET scan (14,15).…”
Section: Discussionsupporting
confidence: 77%
“…As such, there remains significant controversy and uncertainty with regards to the optimal way to integrate it into practice (7)(8)(9)(10). Previous studies have shown the ability of the PET scan to localize disease already thought to be present because of detectable thyroglobulin levels (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The early detection of iodinenegative DTC lesions is important, because it triggers an adjustment in the treatment strategy: surgical resection, external-beam radiation therapy (EBRT), or multikinase inhibitor therapy will be selected rather than 131 I treatment. 18 F-FDG PET/CT is useful for the detection of recurrent DTC lesions, especially in patients with iodine-negative tumors and elevated serum thyroglobulin levels (6)(7)(8)(9)(10). Furthermore, recent studies showed that 18 F-FDG PET can detect DTC lesions more accurately under thyroid-stimulating hormone (TSH) stimulation than under TSH suppression (11)(12)(13).…”
mentioning
confidence: 99%
“…J. Rosenbaum-Krumme и соавт., в дополнение к 1-й тСВТ, выполнили ПЭТ / КТ 90 пациентам с ДРЩЖ и с распространенными стадиями опухоли. По данным авторов, ПЭТ / КТ улучшила начальное стадирование у 9 % пациентов и поменяла тактику ведения пациента в 21 % случаев (главным образом с T3bN1 стадией и от-даленными метастазами): в отношении 12 % пациентов изменилась лечебная тактика, 9 % были назначены до-полнительные методы обследования, результаты кото-рых оказались в дальнейшем очень полезными для уста-новки окончательного первичного диагноза [41].…”
Section: клинические показанияunclassified